A web-based requirements elicitation tool using focus group discussion in supporting computer-supported collaborative learning requirements development - Kasirun, Zarinah Mohd; Salim, Siti Salwah; Perumal, R.M.; Hossain, M.D.; Masud, M.M.; Krishna, L.S.R.; Janardhan, G.R.; Rao, C.S.P.; Sivanandam, S.N.; Pandian, A.P. (Siam Technology College, Bangkok, Thailand, 2009)
Developing correct requirements for any application is vital for the success of the application in any field. Computer-supported collaborative learning (CSCL) has becoming an important tool for enabling collaborative learning (CL) in education. In Malaysia for instance CSCL has been chosen to be a technology enabler to support Smart School project whereby CL has been identified as one of its learning strategies (MOE, 1997). However, the project will not come true if the lacking of CSCL application is not overcome. The situation is more acute as the existing applications are not only general in nature but yet to exhibit collaborative characteristics. This problem is due to many reasons. From the software engineering point of view, first and foremost, the problem is introduced during the elicitation of users needs. A survey carried out by the author had been identified that users are not the first people consulted by courseware developers in eliciting requirements. Furthermore, the courseware developers have no support in carrying out requirements elicitation activity. In conjunction to this, a review was also carried out in requirements elicitation techniques and process. Many methods have been identified and implemented to support requirements elicitation activity. Most of them are group-based, which support the cooperativeness of the requirements elicitation activity. However, the existent of these tools are not recognized in the Malaysian context. Due to this, a new requirements elicitation tool using Focus Group Discussion (FGD) technique is developed based on the survey done and the literature survey carried out. The tool is called FGD-RElicit stands for Focus Group Discussion technique in Requirements Elicitation. This paper focuses on the development of FGD-RElicit from its technique used in supporting elicitation, analysis model, design and architecture. Results of evaluation by the users are also included the paper is wrapped up.